Circulation of Non-SARS-CoV-2 Respiratory Pathogens and Coinfection with SARS-CoV-2 Amid the COVID-19 Pandemic. (8th December 2021) - Uhteg, Katharine; Amadi, Adannaya; Forman, Michael; Mostafa, Heba H
Abstract: Background: Our understanding of the cocirculation of infrequently targeted respiratory pathogens and their contribution to symptoms during the coronavirus disease 2019 (COVID-19) pandemic is currently limited. This research aims at (1) understanding the epidemiology of respiratory pathogens since the start of the pandemic, (2) assessing the contribution of non-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)/influenza/respiratory syncytial virus (RSV) respiratory pathogens to symptoms, and (3) evaluating coinfection rates in SARS-CoV-2-positive patients, both vaccinated and unvaccinated. Methods: Retrospective analysis of respiratory pathogens identified by the Johns Hopkins Diagnostic Laboratory between December 2019 and October 2021 was performed. In addition, we assessed the contribution of respiratory pathogens other than SARS-CoV-2 to symptomatic disease by retesting 2 cohorts of specimens that were (1) collected from symptomatic patients and (2) received limited respiratory pathogen testing. The first cohort was patients who tested negative by the standard-of-care SARS-CoV-2/influenza/RSV testing. The second was a cohort of SARS-CoV-2-positive, symptomatic, fully COVID-19 immunized and unimmunized patients. Results: Between December 2019 and October 2021, a total of 11 806, 62 829, and 579 666 specimens were tested for an extended respiratory panel, influenza/RSV with or without SARS-CoV-2 panel, or SARS-CoV-2, respectively. Positivity rates of different targets differed between different months and were impacted by the COVID-19 pandemic. The SARS-CoV-2-negative cohort had 8.5% positivity for other respiratory pathogens that included primarily enterovirus/rhinovirus (5.8%). In the SARS-CoV-2-positive cohort, no other respiratory pathogens were detected. Conclusions: The COVID-19 pandemic impacted the circulation of certain respiratory pathogens. Other respiratory viral pathogens were associated with symptomatic infections; however, coinfections with SARS-CoV-2 were highly uncommon. Abstract : The COVID-19 pandemic impacted the circulation of seasonal respiratory viruses, however, viral pathogens other than SARS-CoV-2 were associated with symptomatic infections. Coinfections with SARS-CoV-2 remains uncommon even in fully immunized individuals.